ANALISIS PENGARUH INFLASI, NILAI TUKAR , BI RATE TERHADAP TABUNGAN MUDHARABAH PERBANKAN SYARIAH DI INDONESIA PERIODE 2012-2021 - Ajeng Windi Astuti; Anjel Ezania Sihombing; Lutfiah Nur Azizah; Hasyim Hasyim (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study aims to determine the simultaneous and partial effect of inflation, exchange rates and the BI Rate on mudharabah savings in Islamic banking for the period 2012-2021.Mudharabah Savings is the dependent variable while inflation, exchange rate and Bi Rate are the independent variables. The method used in this study is quantitative and processed through a regression analysis tool, namely Eviews. The results of this research study indicate that (1) Inflation has a positive and insignificant effect on Mudharabah Savings (2) Exchange rates have a positive and significant effect on Mudharabah Savings (3) Bi Rate has a negative and significant effect on Mudharabah Savings (4) Inflation, exchange rates and Bi Rate have a significant effect on the Mudharabah Savings.